Indicators of Science, Technology and Innovation - psgim, jcrm (Journal of Contemporary Research in Management (JCRM), 2023)
Albeit the limited resources, India has been trying to increase the budgetary allocations to the Ministries/Departments dealing with Science & Technology, which are engaged in basic/fundamental research and applied research. The Ministries/Departments have been extended special privileges/ perks/incentives with the expectation that young and experienced scientists and engineers would address the basic problems faced by vast majority population and science and technology will be an important growth engine for the progress of the country. Consuming the budget allocated, recruiting more number of scientific and technical staff, setting up new laboratories, starting new projects/schemes, publication of articles in international peer reviewed journals, etc. are the parameters by which the efficacy of the organizations is now measured. Do these measure the real worth and output of these organizations? Are they adequate? What is the practice followed in other developed countries? This paper attempts to find out the indicators of Science, Technology and Innovation in different countries and identify the indicators which can be used for evaluating the selected Scientific Organizations in Government sector. This will help in Strategic Management Process from public policy perspective. Key Words: Science, Technology & Innovation (STI), Indicators, Performance Measurement Tools, Public Policy, R & D Intensity, Research Outcomes Recognizing the potential of science, technology and innovation, several organizations have been established in government sector, either purely as Government Organizations or as autonomous institutions. Other Laboratories/Institutions have been set up by private or public private participation for pursuing science or together with academic component. In addition many non-governmental bodies, associations of scientists, etc. are also involved in Science, Technology and Innovation in different countries. The efforts of these organizations have yielded development of several technologies and products of daily use. Innovation and technology are used to further the improvements for wealth generation and better quality of life. Heavy investment is made in creating infrastructure, manpower and other resources for this purpose. While the innovations leading to development of technologies is the testimony for the status of life today in many developed countries, the degrees of deployment vary on the level of investment, availability of facilities in lab scale and industry level as also availability of skilled manpower in other countries.